Cilostazol increases patency and reduces adverse outcomes in percutaneous femoropopliteal revascularisation: a meta-analysis of randomised controlled trials. Issue 1 (4th November 2014) - Benjo, Alexandre M; Garcia, Daniel C; Jenkins, J Stephen; Cardoso, Rhanderson M N; Molina, Taina P; El-Hayek, Georges E; Nadkarni, Girish N; Aziz, Emad F; Dinicolantonio, James J; Collins, Tyrone
Abstract : Background: Cilostazol is an oral antiplatelet agent currently indicated for treatment of intermittent claudication. There is evidence that cilostazol may reduce femoropopliteal restenosis after percutaneous endovascular intervention. Methods: We searched PubMed, Scopus and Cochrane databases from 1966 through September 2013 for randomised controlled trials (RCTs) evaluating the addition of cilostazol to standard care in patients receiving femoropopliteal endovascular treatment. Restenosis, target lesion revascularisation and combined adverse outcomes (death, revascularisation and amputation) within 1–2 years postprocedure were evaluated. Results: Of 205 articles, three RCTs were included in the analysis. The pooled data provided a total of 396 patients, 195 of whom received cilostazol. When compared to standard medical therapy alone, cilostazol significantly reduced the risk of restenosis (risk difference −0.20; 95% CI −0.29 to −0.11; p<0.0001; number needed to treat 5), target lesion revascularisation (risk difference −0.17; 95% CI −0.25 to −0.09; p<0.0001; number needed to treat 6). Death and amputation were not different in between groups. Conclusions and limitation: Cilostazol significantly increases femoropopliteal patency and decreases adverse outcomes in percutaneous endovascular intervention. However, further RCTs are needed because of limited sample size; this meta-analysis represents the best current evidence.